Stabilization of Lateritic Soil using Fly Ash Based Geopolymer - M.M. Ahmad; R.A. Razak; M.M. Al Bakri Abdullah; K. Muhamad; A.O. Mydin; A.V. Sandu (Archives of Metallurgy and Materials)
Current development consists of a high-rise building and heavy traffic load demands for soil with good engineering properties. Lateritic soil is commonly treated with Ordinary Portland Cement (OPC) to improve its engineering properties in order to enhance its load bearing capacity. The production of OPC however emits a large amount of carbon dioxide (CO2) into the atmosphere. Geopolymer technology has been explored as an alternative replacement for the OPC. In this research, the unconfined compressive strength (UCS) of a lateritic soil treated with fly ash (FA) based geopolymer up to 40% by weight of the dry soil and activated using combination of sodium silicate (Na2SiO3) and sodium hydroxide (NaOH) was investigated by means of unconfined compression test (UCT). The effect of different molarity of NaOH (5-20 M), FA to alkali activator (AA) ratio (1-3) and different curing temperatures to the UCS of treated soil sample are being determined. In general, as the content of FA in the soil increases, the UCS increases more than 100% and almost 400% compared to the untreated soil for room curing temperature and oven curing temperature respectively. Based on the scanning electron microscopy (SEM) result, the molarity of NaOH solution reduces the pores in the treated soil sample. The geopolymerization process combines the soil particle and makes it denser, resulting in higher UCS than the untreated soil sample.